Emerging challenges in technical vocational education and training of Pakistan in the context of CPEC - Naila Bano; Siliu Yang; Easar Alam (Economies, 2022)
Pakistan is a country with rich natural and human resources. The role of highly skilled people in national development has become enormously vital in the new developmental period, but it is also an irrefutable fact that the gap in highly skilled personnel in Pakistan is expanding. The organization of Technical Vocational Education and Training was introduced to prepare a skilled workforce for various industries and sectors in Pakistan; however, the 60% level of young, unskilled, and semi-skilled labor emerging from informal and non-formal sectors is largely attributed to the failure of Technical Vocational Education and Training to supply the country with its requirements for trained manpower for the economy and China Pakistan Economic Corridor (CPEC) projects. China and Pakistan launched historic projects such as CPEC as part of the Belt and Road Initiative (BRI), which fostered economic cooperation and development between the two countries. This article will go through the overview and the course of Technical Vocational Education and Training (TVET) in Pakistan. The major purpose of this study is to highlight that TVET in general, and CPEC in particular, are suffering from a lack of qualified personnel because of a variety of other reasons, such as outdated equipment, a lack of industry connectivity, inadequate skills, unemployment, and so on. The study is descriptive and exploratory in nature, and it employs a qualitative research method. The perspectives of the TVET challenges in Pakistan were researched using the data obtained from 500 student and staff respondents, including teachers, TVET workers, and TVET job holders. Some of the important findings include the fact that the current state of the TVET institutions is no doubt due to infrastructural issues and a lack of funding. In addition, TVET in Pakistan is marked by inadequate skills, a lack of industry connectivity, unemployment, insufficient teacher training, and a lack of female participation. In this study, recommendations were given based on the research analysis and research findings.
Keywords: 330; challenges; CPEC; Pakistan; technical vocational education and training